The abscopal effect of anti-CD95 and radiotherapy in melanoma - Jixiang Xu; JiangFeng He; JiaJun He; Yuanmin He; DaoJun Zhang; Rui Kong; Kena Dan (Discover Oncology, 2023)
Abstract Background Radiotherapy (RT) is frequently adopted to control cancer cell proliferation, which is achieved by altering the tumor microenvironment (TME) and immunogenicity. Apoptosis of cancer cells is the major effect of radiation on tumor tissues. Fas/APO-1(CD95) receptors on the cell membrane are death receptors that can be activated by diverse factors, including radiation and integration with CD95L on CD8+ T cells. The abscopal effect is defined as tumor regression out of the local RT field, and it is produced through anti-tumor immunity. The immune response against the radiated tumor is characterized by the cross-presentation between antigen-presenting cells (APCs), which includes cytotoxic T cells (CTLs) and dendritic cells (DCs). Methods The effect of activation and radiation of CD95 receptors on melanoma cell lines was examined in vivo and in vitro. In vivo, bilateral lower limbs were given a subcutaneous injection of a dual-tumor. Tumors in the right limb were radiated with a single dose of 10 Gy (primary tumor), while tumors in the left limb (secondary tumor) were spared. Results The anti-CD95 treatment plus radiation (combination treatment) reduced growth rates of both primary and secondary tumors relative to the control or radiation groups. In addition, higher degrees of infiltrating CTLs and DCs were detected in the combination treatment compared to the other groups, but the immune response responsible for secondary tumor rejection was not proven to be tumor specific. In vitro, combination treatment combined with radiation resulted in further apoptosis of melanoma cells relative to controls or cells treated with radiation. Conclusions Targeting CD95 on cancer cells will induce tumor control and the abscopal effect.